Partisan politics and privatization in OECD countries - Zohlnhöfer, Reimut; Obinger, Herbert; Schmitt, Carina (Comparative political studies, 2014)
Many scholars have argued that partisan differences have disappeared since the 1980s due to ever increasing economic globalization and the deepening of European integration. Using a new primary data set on public ownership that contains detailed information on privatization in 20 countries between 1980 and 2007, we test these claims empirically in relation to state ownership. We pay special attention to the question of whether changes in the international political economy, notably globalization and different aspects of European integration, condition partisan politics. Our empirical findings suggest that political parties have continued to significantly shape national privatization trajectories in line with the classic partisan hypothesis. While partisan differences are somewhat reduced by the liberalizing and market-building efforts of the EU, globalization does not condition partisan effects. Moreover, the run-up to EMU even seems to have reinforced partisan differences.